PEMBUATAN KARDIGAN ECO PRINT ANTI DROPLET SEBAGAI FASHION ERA NEW NORMAL - Tsabbita, Afifatu; Khasanah, Sarifatun; Asfiyah, Parni; Sari, Mia Luvita; Hamidah, Siti Nur; Retnasari, Dian (Prosiding Pendidikan Teknik Boga Busana, 2023)
In the new normal era, Indonesian people have carried out various activities such as before the existence of COVID-19. The new normal era itself does not represent that the covid-19 virus is completely gone. Based on JHU CSSE Covid-19 data as of June 16, 2022 to July 16, 2022, there was an increase in cases from 1173 to 4329. The Covid-19 condition makes people have to keep themselves away from Covid-19 transmission through droplets. For people who work or carry out activities outside the home, they are vulnerable to contracting the Covid-19 virus, so clothing is needed to prevent droplet splashes. The purpose of making these clothes is as a solution to prevent the transmission of COVID-19 through patient droplets. Based on the results of a survey in March 2021 through a google form filled out by 104 respondents aged 18-55 years, 66.3% of respondents like cardigans as outerwear. The ecoprint technique supports trends in the fashion sector, namely eco fashion which is developing and in demand. The Sriwedari anti droplet ecoprint cardigan is designed to protect itself from droplet exposure because it uses cotton twill woven fabric which is water repellant. The Sriwedari Javanese ecoprint cardigan product applies ecoprint and Sriwedari script patterns as an aesthetic value. The merging of these two decorations aims to preserve the culture of loving the environment and Javanese script. Keywords: : covid-19, droplet's anti, ecoprint, cardigan, Sriwedari Javanese script